HUBUNGAN PENGETAHUAN TENTANG KEHAMILAN TIDAK DIINGINKAN (KTD) DENGAN PERILAKU SEKSUAL MAHASISWA FAKULTAS KESEHATAN MASYARAKAT UIN SUMATERA UTARA 2023 - Suci Wahyuni; Putra Apriadi Siregar (CV. Adiba Aisha Amira, 2023)
Reproductive health issues are still a major improvement for the government that require special attention, one of which is unwanted pregnancies (KTD). Unwanted pregnancies (KTD) have a significant impact on the reproductive health, emotional and social well-being of the individuals involved. One of the vulnerable groups for KTD is university students, because they are at reproductive age who are active and are involved in sexual behavior. The purpose of this study was to find out the relationship between the level of knowledge and sexual behavior of students at the Faculty of Public Health, UIN North Sumatra. This research is a quantitative analytic study with a cross sectional approach. The study population was all students of the Faculty of Public Health, State University of North Sumatra using a simple random sampling technique of 32 students. Data was obtained by filling out a questionnaire in the Google form and then distributing it. Then the data were analyzed using SPSS. Univariate and bivariate data analysis using the Chi Square test. The results of the research are the knowledge level category with very good sexual behavior (37.5%) and the knowledge level category is very knowledgeable with good sexual behavior (12.5%) using the Chi Square test with a p-value (0.000) < α (0.005) . That there is no relationship between knowledge about unwanted pregnancies (KTD) and sexual behavior of students at the Public Health Faculty of UIN North Sumatra.